Inovasi Digital dalam Manajemen Keamanan Sekolah: Studi Penggunaan Aplikasi “Ali Topan” untuk Mengatasi Perundungan - Abdul Majid (Universitas Muhammadiyah Bangka Belitung, 2025)
Bullying is a serious issue in the educational environment that affects students' safety and well-being. This study aims to analyze the implementation of school principal management in the actuating phase of the bullying reduction program using the